2018
DOI: 10.3390/ijms19113290
|View full text |Cite
|
Sign up to set email alerts
|

Identification, Structural Characterization and Gene Expression Analysis of Members of the Nuclear Factor-Y Family in Chickpea (Cicer arietinum L.) under Dehydration and Abscisic Acid Treatments

Abstract: In plants, the Nuclear Factor-Y (NF-Y) transcription factors (TFs), which include three distinct types of NF-YA, NF-YB, and NF-YC TFs, have been identified to play key roles in the regulation of various plant growth and developmental processes under both normal and environmental stress conditions. In this work, a total of 40 CaNF-Y-encoding genes, including eight CaNF-YAs, 21 CaNF-YBs, and 11 CaNF-YCs, were identified in chickpea, and their major gene and protein characteristics were subsequently obtained usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 86 publications
1
10
0
1
Order By: Relevance
“…In this study, CsaNF-YA genes contained 2-5 introns, and multiple intron/exon organizations were observed for NF-YB and NF-YC genes (Figure 4), which is in agreement with previous studies, revealing the conserved features of the evolution of these subunits in plants. In addition, the CsaNF-YBs (7/13) and CsaNF-YCs (3/7) were prevalently lack of introns (Figure 4), which is a universal feature of NF-YB and NF-YC genes in other plant species, such as peach, in which 6 out of 12 NF-YBs and 4 out of 6 NF-YCs have no introns [14]; tea plant, in which 7 out of 15 NF-YBs and 6 out of 10 NF-YCs have no introns [16]; castor bean, in which 8 out of 12 NF-YBs and 3 out of 7 NF-YCs have no introns [15]; chickpea, in which 11 out of 21 NF-YBs and 7 out of 11 NF-YCs have no introns [43]; and banana, in which 12 out of 16 NF-YBs and 12 out of 14 NF-YCs have no introns [18]. The similar conserved domain arrangements and intron/exon organizations in each subunit indicate that NF-Y genes are highly conserved during the evolution of plants, which may contribute to their crucial biological functions.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, CsaNF-YA genes contained 2-5 introns, and multiple intron/exon organizations were observed for NF-YB and NF-YC genes (Figure 4), which is in agreement with previous studies, revealing the conserved features of the evolution of these subunits in plants. In addition, the CsaNF-YBs (7/13) and CsaNF-YCs (3/7) were prevalently lack of introns (Figure 4), which is a universal feature of NF-YB and NF-YC genes in other plant species, such as peach, in which 6 out of 12 NF-YBs and 4 out of 6 NF-YCs have no introns [14]; tea plant, in which 7 out of 15 NF-YBs and 6 out of 10 NF-YCs have no introns [16]; castor bean, in which 8 out of 12 NF-YBs and 3 out of 7 NF-YCs have no introns [15]; chickpea, in which 11 out of 21 NF-YBs and 7 out of 11 NF-YCs have no introns [43]; and banana, in which 12 out of 16 NF-YBs and 12 out of 14 NF-YCs have no introns [18]. The similar conserved domain arrangements and intron/exon organizations in each subunit indicate that NF-Y genes are highly conserved during the evolution of plants, which may contribute to their crucial biological functions.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al [59] reported that most of the NF-YB contained only one exon, and the genes from the same clade displayed a similar motif pattern in Gossypium hirsuyum . Chu et al [60] reported 5 exons and 4 introns (6 genes) or 6 exons and 5 introns (2 genes) in CaNF-YA gene family members in Cicer arietinum . Further, they noticed 1 to 6 exons in CaNF-YB family, and 7 intronless out of 11 members in the CaNF-YC family.…”
Section: Discussionmentioning
confidence: 99%
“…Further, several members of the NF-YB and NF-YC have been found without any introns like in S . bicolor [55], Ricinus cummunis [34] and chickpea [60]. Introns are essential parts of all eukaryotic genes.…”
Section: Discussionmentioning
confidence: 99%
“…In castor bean, 25 RcNF-Y genes have been identified across the genome and their expression changes were investigated under four types of abiotic stresses (drought, cold, heat and salt stresses) [44, 45]. In chickpea, a total of 40 CaNF-Y genes have been identified and some CaNF-Y genes were found to be responsive to dehydration and abscisic acid treatments [9].…”
Section: Introductionmentioning
confidence: 99%